Rancang Bangun Robot Tank Automatik Pendeteksi Halangan dengan Kendali Fuzzy Logic - Badidi, Julianto Rebbi; Asri, Ervan; Aisuwarya, Ratna (Universitas Andalas, 2018)
Robotics is a field of science that is developing rapidly, One of Robotic field is a wheeled robot whose sample application allows robots to explore automatically. But today, more research on the application of artificial intelligence in robot control is aimed at obtaining sophisticated kinematic control. In this final project, a wheeled robot will be designed with the ability to detect obstacles. As a control object is a robot tank that both wheels use a belt wheel and have a separate DC motor. A fuzzy logic controller functions to regulate the speed and direction of the robot's motion based on the input of the ultrasonic sensor. The design of robots based on the embedded microcontroller is designed using the C language. From the test results, that fuzzy logic can be embedded in the ATmega328 microcontroller control unit on Arduino Uno, so that a robotic motion can be avoided that can avoid obstacles properly. The closer the obstacle distance results in the sharpening direction of the robot and the more rigorous robot movement.